(NkOSTQNTINA(B. (NsER)QÆQ LISTÆWOK DO (B150-(NRÆ^^Q Z DNQ NARODVENNQ UKRAÇNSXKOÇ PISXMENNICÆ kOSTQNTINI mALICXKOÇ (B/s)E - (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NgLADI[(B-(NdVURAN(B, (Nn(B.s ((NnATAL)QÆQ(B)s)E; (NgRIGOR^UK(B-(NwOJTKO(B, (Nn(B. (Nw(B.s ((NnATAL)QÆQ wOLODIMIRÆWNA(B)s)E; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdOWBU[(B, (No(B. )Qæ.s)E ((NoLEKSANDR )QæWANOWI^(B)s)E; (NkORN)QÆJ^UK(B, (Nw(B.s)E ((NwALENTINA(B)s; (NtARAS@K(B, (Ng(B. (Nt(B.s ((NgALINA tIMOF)QÆÇWNA(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2022)
(NsER)QÆQ LISTÆWOK (B"(NkOSTQNTINA(B" (NDO (B15(NRÆ^^Q Z DNQ NORODVENNQ UKRAÇNSXKOÇ PISXMENNICÆ kOSTQNTINI mALICXKOÇ WIJLA W SWÆT U WIDAWNICTWÆ (B"(NrODOWÆD(B". (N~ERGOWA SERÆQ LISTÆWOK WIJ[LA ZAWDQ^U@^I SPECÆALXNOMU PROÃKTU ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI(B. (NsWQTÆJ DATÆ (B- 150-(NRÆ^^Q Z DNQ NARODVENNQ SLAWETNOÇ ZEMLQ^KI (B- (N^ERGOWÆ PRISWQTI UKRAÇNSXKIH POETÆW(B.s)E
(NsPEC)QÆALXNIJ Æ BLAGODÆJNIJ PROÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI Æ mAMAÇWSXKOÇ TERITORÆALXNOÇ GROMADIs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E